Clima organizacional y su relación con el desempeño laboral en la empresa Pukuni Consultores y Servicios Generales S.A.C, Iquitos 2021 - Alvarado Torres, Jose Carlos (2022)
The objective of this research was to determine the relationship between the organizational climate and job performance in the workers of the company PUKUNI consultants and general services SAC, Iquitos - 2021. The total sample was made up of 20 employees of the company PUKUNI consultants and general services. SAC, was obtained as a result that shows us a value of Pearson connections equal to 0.881, which indicates a connection can from lateral to lateral, 0.000; according to the Decision Rule, comparing the p-Value calculated by the data with the theoretical p-Value of Table = 0.05. If the calculated p-value is greater than or equal to 0.05, Ho will be accepted. But, if the calculated p-value is less than 0.05, Ha will be accepted. According to the value obtained, we confirm that the alternative hypothesis is accepted and the null hypothesis is rejected; then, it was concluded that the hypothesis "There is a high relationship between the organizational climate and job performance in the workers of the company PUKUNI CONSULTORES Y SERVICIOS GENERALES S.A.C, Iquitos - 2021" is accepted.